Down‐Regulation of Dkk‐1 in Platelets of Patients With Axial Spondyloarthritis. Issue 10 (30th August 2021) - Czepiel, Marcin; Stec, Małgorzata; Korkosz, Mariusz; Guła, Zofia; Błyszczuk, Przemysław; Baran, Jarosław; Siedlar, Maciej
Abstract : Objective: Axial spondyloarthritis (SpA) is a chronic autoinflammatory disease with new bone formation, which is controlled by Wnt/β‐catenin signaling. Dkk‐1 is an inhibitor of the Wnt pathway, and in humans, platelets represent a major source of Dkk‐1. This study was undertaken to investigate whether levels of Dkk‐1 in serum and platelet expression of DKK1 messenger RNA (mRNA) and Dkk‐1 protein are affected in patients with axial SpA compared to healthy controls. Methods: Forty‐one patients with axial SpA and 35 healthy controls were enrolled in the study. Total serum Dkk‐1 levels in all patients and healthy controls were measured by quantitative enzyme‐linked immunosorbent assay. Platelet DKK1 mRNA was analyzed by quantitative reverse transcriptase–polymerase chain reaction in 20 patients with axial SpA and 20 controls, and Dkk‐1 protein levels were measured by immunoblotting in 20 patients with axial SpA and 18 controls. Results: We found a lower concentration of Dkk‐1 in the serum from patients with axial SpA compared to the serum from healthy controls ( P < 0.0001). Furthermore, the expression of Dkk‐1 was significantly reduced both at the transcriptional level ( P < 0.04) and at the protein level ( P < 0.007) in platelets isolated from the blood of patients with axial SpA. Conclusion: Our preliminary observations suggest that dysfunction of the megakaryocyte/platelet axis might be responsible for reduced serum Dkk‐1 levels in patients with axial SpA. Dkk‐1 is down‐regulated in the platelets of patients with axial SpA, a mechanism that might play a role in new bone formation.